Sscience School - "Manning,mick" (Kingfisher: London, 1999)
A fun & original approach to science, this book is packed with illustrations & experiments to do, using things easily found at home. It is interactive & the fascinating experiments help children grasp the basic concepts of science
Keywords: Science-Experiments